## PLEASE ANSWER FAST! 20 POINTS+BRAINLIEST!!! 1. factor: k^2+2k-24 2. factor: 4k^2-1 3. factor: 25b^2-30b+9 4. solve b

Question

1. factor: k^2+2k-24
2. factor: 4k^2-1
3. factor: 25b^2-30b+9
4. solve by factoring: x^2+11x+28=0

in progress 0
2 weeks 2021-11-15T11:52:51+00:00 2 Answers 0 views 0

1.  k^2+2k-24

1A. (k – 4) (k + 6)

2. 4k^2-1

2A. (2k + 1) (2k – 1)

3. 25b^2-30b+9

3A. (5b – 3)^2

4. x^2+11x+28=0

4A. x = (-4) OR (-7)

5. (3a+8)(3a^2-a-7)

5A. 9a^2 + 21a^2 – 29a – 56

Step-by-step explanation:

1.  k^2+2k-24

Factor using the AC factoring method.

k^2 = 2k

2k + 2k – 24

(k – 4) (k +6)

2. 4k^2-1

Use the Difference of Squares Formula: a^2 – b^2 = (a + b)(a – b)

2k = a

1 = b

(2k + 1)(2k – 1)

3. 25b^2-30b+9

Use the perfect square rule

(5b – 3)(5b – 3)

(5b – 3)^2

4. x^2+11x+28=0

Factor, by setting each factor equal to 0

x^2+11x+28=0

(x + 4)(x + 7) = 0

x = (-4) OR (-7)

5. (3a+8)(3a^2-a-7)

Simply, multiply each term in the first expression by each term in the second expression, and then simplify.

(3a+8)(3a^2-a-7)

9a^2 + 21a^2 – 29a – 56

1.(k−4)(k+6)

Explain:Factor k2+2k−24

k2+2k−24

=(k−4)(k+6)

2.(2k+1)(2k−1)

Factor 4k2−1

4k2−1

=(2k+1)(2k−1)

3.(5b−3)(5b−3)

Explain: Factor 25b2−30b+9

25b2−30b+9

=(5b−3)(5b−3)

4.x=4 or x=-7

x2+11x+28=0

Step 1: Factor left side of equation.

(x+4)(x+7)=0

Step 2: Set factors equal to 0.

x+4=0 or x+7=0

x=−4 or x=−7

is  5 to help solve or are they questions to?

Step-by-step explanation: